(untitled) (Contrastive Linguistics, 2024)
Мартин Стефанов. Номинализацията на предиката в сръбския и българския книжовен език от края на XIX и началото на XX век. Електронна публикация. Факултет по славянски филологии. Филологически форум – Experior, ноември 2023, 240 с. Martin Stefanov’s monograph examines the processes of nominalization of the predicate, but the author has set himself the goal of doing this in a comparative plan between the Serbian and Bulgarian languages, at the end of the 19th and the beginning of the 20th century. Both nominalized constructions and periphrastic predicates are explained in detail. The main stylistic and textual characteristics of the nominalizations are also presented.